ENFERMEDAD DE BOWEN TRATADA CON CRIOTERAPIA COMBINADA CON IMIQUIMOD TOPICO AL 5%. TRATAMIENTO ALTERNATIVO A LA CIRUGÍA EN PACIENTES MAYORES CON CO-MORBILIDADES - Lezcano Liz (Nasza Dermatologia Online, 2011)
Bowen's disease (BD) is an in situ squamous cell carcinoma in which dysplastic changes occur throughout the full thickness of the epidermis. It usually affects fair-skinned people over 60 years. It is characterized by erythematous papules and plaques solitary or multiple, with a slow centrifugal growth. The differential diagnosis of BD should be established with chronic dermatoses such as psoriasis, chronic eczema, superficial basal cell carcinoma and Paget's disease of the skin. Only 5% of cases progress to invasive squamous cell carcinoma. We report the case of a woman of 63 years of age with BD treated with cryotherapy combined with topical 5% imiquimod who responded adequately to this combination therapy.